2007
DOI: 10.1080/03014220709510071
|View full text |Cite
|
Sign up to set email alerts
|

Minimum specifications for transmissible transgenic biocontrol agents for brushtail possum (Trichosurus vulpecula) population eradication

Abstract: I consider how two fundamental aspects of parasitology and population genetics-macroparasite aggregation among hosts and the HardyWeinberg principle-govern the theoretical impact of transgenic forms of a possum-specific nematode Parastrongyloides trichosuri, that cause female infertility, on brushtail possum (Trichosurus vulpecula) populations. Assuming chromosomal inheritance of transgenes, the conditions under which transgenic P. trichosuri would be an efficacious tool for eradication are predicted to be sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Fertility control of pest species provides a theoretically and practically plausible approach to pest management (Courchamp and Cornell ; Cowan et al. ), but the development of such approaches has been slow (Tompkins ; Arthur et al. ; Cross et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility control of pest species provides a theoretically and practically plausible approach to pest management (Courchamp and Cornell ; Cowan et al. ), but the development of such approaches has been slow (Tompkins ; Arthur et al. ; Cross et al.…”
Section: Introductionmentioning
confidence: 99%
“…Worms expressing the model heterologous gene beta-galactosidase showed variable inheritance between different transgenic lines, although all lines were shown able to establish patent infections and the model transgene was transmitted effectively from the parasitic adult to the free-living progeny. In addition, however, modelling has indicated that parasite aggregation in hosts could result in many possums bearing low worm burdens, which may not result in sufficient antigenic exposure to invoke a sterility-inducing immune response (Tompkins 2007). Third, the potential for longterm persistence of a transgenic strain in the field is unknown, since any fitness cost of transgenesis would put recombinant worms at a competitive disadvantage with wild-type strains.…”
Section: Species-specific Infectious Agents As Transmissible Vectors:mentioning
confidence: 99%
“…Gilna et al 2005;Henderson & Murphy 2007;Cowan et al 2008) and, particularly in the case of transmissible GM vectors, the concerns raised may be of sufficient magnitude to discourage development of a fertility-control vaccine based on such a vector. Hence, organisms that are either nontransmissible or have imperfect transmission or transgene inheritance (such that the organism and/or transgene persists long enough to cause possum population suppression, but fails to persist in the long term) are likely to be more acceptable to Australian regulatory authorities (Tompkins 2007).…”
Section: Species-specific Infectious Agents As Transmissible Vectors:mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, these approaches are generally more effective at rapidly reducing population size in pest species with relatively high fecundity, low survivorship rates and short generation times [20]. However, the development of such 'fertility control' to date has been less than promising, with technologies either unable to reach the levels of efficacy required [21][22][23], or having undesirable non-target effects [24,25]. Arguably, the most successful of these approaches to date has been the sterile male technique (SMT) commonly applied to invertebrate pests [26,27], in which large numbers of sterile males (SMs) are released into a population each generation.…”
Section: Introductionmentioning
confidence: 99%